Novel bacteriocinogenic Lactobacillus plantarum strains and their differentiation by sequence analysis of 16S rDNA, 16S-23S and 23S-5S intergenic spacer regions and randomly amplified polymorphic DNA - Moghadam, Morteza Shojaei; Foo, Hooi Ling; Leow, Thean Chor; Abdul Rahim, Raha; Loh, Teck Chwen (Faculty of Food Technology and Biotechnology, University of Zagreb, 2010)
Six strains of bacteriocinogenic Lactobacillus plantarum (TL1, RG11, RS5, UL4, RG14 and RI11) isolated from Malaysian foods were investigated for their structural bacteriocin genes. A new combination of plantaricin EF and plantaricin W bacteriocin structural genes was successfully amplified from all studied strains, suggesting that they were novel bacteriocin- producing L. plantarum strains. A four-base pair variable region was detected in the short 16S-23S intergenic spacer regions of the studied strains by a comparative analysis with 17 L. plantarum strains deposited in the GenBank, implying they were new genotypes. The studied L. plantarum strains were subsequently differentiated into four groups on the basis of the detected four-base pair variable region of the short 16S-23S intergenic spacer region. Further analysis of the DNA sequence of 23S-5S intergenic spacer region revealed only one type of 23S-5S intergenic spacer region present in the studied strains, indicating it was highly conserved among the studied L. plantarum strains. Three randomly amplified polymorphic DNA experiments using three different combinations of arbitrary primers successfully differentiated the studied L. plantarum strains from each other, confirming they were different strains. In conclusion, the studied L. plantarum strains were shown to be novel bacteriocin producers and high level of strain discrimination could be achieved with a combination of randomly amplified polymorphic DNA analysis and the analysis of the variable region of short 16S-23S intergenic spacer region present in L. plantarum strains.